Ultrasound-Triggered Liposomes Encapsulating Quantum Dots as Safe Fluorescent Markers for Colorectal Cancer - Nahid S. Awad; Mohamed Haider; Vinod Paul; Nour M. AlSawaftah; Jayalakshmi Jagal; Renu Pasricha; Ghaleb A. Husseini (MDPI AG, 2021)
Quantum dots (QDs) are a promising tool to detect and monitor tumors. However, their small size allows them to accumulate in large quantities inside the healthy cells (in addition to the tumor cells), which increases their toxicity. In this study, we synthesized stealth liposomes encapsulating hydrophilic graphene quantum dots and triggered their release with ultrasound with the goal of developing a safer and well-controlled modality to deliver fluorescent markers to tumors. Our results confirmed the successful encapsulation of the QDs inside the core of the liposomes and showed no effect on the size or stability of the prepared liposomes. Our results also showed that low-frequency ultrasound is an effective method to release QDs encapsulated inside the liposomes in a spatially and temporally controlled manner to ensure the effective delivery of QDs to tumors while reducing their systemic toxicity.